Mineral metabolism markers and the long-term risk of hip fracture: the cardiovascular health study. - Robinson-Cohen, Cassianne; Katz, Ronit; Hoofnagle, Andrew N; Cauley, Jane A; Furberg, Curt D; Robbins, John A; Chen, Zhao; Siscovick, David S; de Boer, Ian H; Kestenbaum, Bryan (J Clin Endocrinol Metab, 2011)
CONTEXT: Disturbances in mineral metabolism are associated with lower bone mineral density and fracture; however, previous human studies have assessed individual mineral metabolism markers in isolation. OBJECTIVE: We assessed serum concentrations of 25-hydroxyvitamin D (25-OHD), PTH, and bone-specific alkaline phosphatase (BAP) concentrations individually, and in combination, in association with the long-term risk of hip fracture among a general population of older adults. DESIGN AND SETTING: We studied 2294 participants from the Cardiovascular Health Study (mean age 74 yr) who were ambulatory and free of hip fracture and known cardiovascular disease at baseline. We used proportional hazards models to evaluate associations of baseline serum 25-OHD, PTH, and BAP concentrations with the time to first hospitalized hip fracture. RESULTS: During a median of 13 yr of follow-up, 242 participants (10.6%) developed an incident hip fracture. Serum 25-OHD concentrations less than 15 ng/ml were associated with a 61% greater adjusted risk of fracture (95% confidence interval 12-132% greater). In contrast, neither serum PTH nor BAP concentrations were significantly associated with fracture risk. The association of 25-OHD deficiency with hip fracture was not significantly altered by either PTH or BAP concentrations. CONCLUSIONS: Serum concentrations of 25-OHD, but not PTH or BAP, are associated with long-term hip fracture risk among ambulatory older adults. These data suggest that 25-OHD is the most relevant mineral metabolism marker of fracture risk among older people.
Keywords: Aged; Aged, 80 and over; Alkaline Phosphatase; Biomarkers; Bone Density; Female; Hip Fractures; Humans; Male; Parathyroid Hormone; Risk; Vitamin D